The relationship between Chinese vocational college students' adverse childhood experience and meaning in life: the mediating role of self-esteem and the moderating role of humorous coping - Yun, Ai; Cai, Yi; Hu, Yuanyan (Frontiers in Psychology, 2025)
This study examined the relationship between adverse childhood experiences (ACEs) and meaning in life among Chinese vocational college students, along with the mediating role of self-esteem and the moderating role of humorous coping. A total of 451 students were assessed utilizing the Adverse Childhood Experiences Scale (ACES), the Meaning in Life Questionnaire (MLQ), the Rosenberg's Self-Esteem Scale (RSES), and the Coping Humor Scale (CHS). Results indicated that: (1) adverse childhood experiences significantly and negatively predicted meaning in life; (2) self-esteem partially mediated the relationship between adverse childhood experiences and meaning in life; (3) humorous coping moderated the first stage of the mediation model, specifically buffering the negative effect of adverse childhood experiences on self-esteem. In summary, adverse childhood experiences reduce meaning in life by impairing self-esteem, whereas enhancing humorous coping abilities can buffer their detrimental effects on self-esteem among college students.